Changes in the hemostatic system in severely ill COVID-19 patients - Milenković, Marija; Kovač, Mirjana; Rović, Ivan; Šijan, Đuro; Crnokrak, Bogdan; Zdravković, Marija (Medical Research, 2024)
Introduction/research objective: COVID-19 coagulopathy is a disorder of the hemostatic system that occurs in critically ill patients infected with the SARS-CoV 2 virus and increases the risk of mortality. The goal of the research is to evaluate changes in hemostatic parameters and determine their prognostic significance in patients with a severe form of the COVID-19 disease. Methods: The study was designed as a retrospective cohort study, which included 146 patients treated from June to September 2020 in the Intensive Care Unit (ICU) of the Clinical Hospital Center ”Bežanijska Kosa” in Belgrade, diagnosed with COVID-19 pneumonia. Inclusion criteria were age over 18 years, proven current SARS-CoV2 infection and admission to ICU. Results: 82 patients (56.2%) died during the treatment, while 64 (43.8%) were discharged. Significantly higher D-dimer values ​​on admission to the ICU were recorded in subjects who died during treatment 888 (1226.5)ng/ml compared to persons who were discharged from treatment 666 (1207.3)ng/ml (p = 0.03). Differences were not demonstrated for INR, aPTT and fibrinogen. D-dimer values ​​on admission to the ICU greater than or equal to 760ng/ml are a statistically significant predictor of death during hospitalization (p = 0.04). Conclusion: COVID coagulopathy is a complication that increases the mortality of people infected with the SARS-CoV2 virus. The main feature is a state of hypercoagulability, which is detected by elevated D-dimer values. D-dimer greater than or equal to 760 ng/ml on admission to the ICU may have prognostic significance for survival during hospitalization.